URGENSI KOMUNIKASI POLITIK DAKWAH - Suharto, Suharto (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2013)
Political communication is a  kind of communication which involves political messages and  actors, or  it is related to power, state, and government policy. Based on this definition, as an  applied science, political communication is not something new. It can be also understood as a communication between ''the  ruler" and  ''the  ruled". To communicate politics without a concrete political action can be actually carried by anyone, such as students, lecturers, and so on. The same also applies to political communcation of da'wah,  which is not relatively different from political communication in general. It is obligatory that all preachers should be able to plan their da'wah activities which are more structured and concrete. This aims not only to transfer knowledge or da'wah  messages, but also to give strong impacts to decision makers who are sinergized with power